Prospects For Improving The Efficiency Of Human Resources In Uzbekistan - Alimardonova Gulifzoda Alimardon kizi (Academia One Publishing, 2024)
Prospects for improving the efficiency of human capital in Uzbekistan are economic development of entrepreneurship and social modernization of education, bringing society to a high example of welfare and human value.
Keywords: Human; education; potential